Rh-D-primigravida mother with anti Rh-17 antibodies causing mild haemolytic disease of foetus and newborn in baby: a case report (Bangladesh Journal of Medical Science, 2021)
Rh-D- is an unusual phenotype in Rh blood group system, lacking all Cc or Ee antigens but demonstrates a stronger D antigen expression. We describe here an extremely rare Rh-D phenotyped mother with first baby affected by haemolytic disease of foetus and newborn (HDFN). A 20-year-old pregnant lady, presented in active labour with foetal distress and planned for emergency cesarean section. Her blood group was A RhD positive, with positive antibody screening. Antibody identification demonstrated multiple antibodies against RhCc Ee polypeptide by the reference laboratory. Rh phenotype was -D-/-D- with no C/c and E/e antigen but strong D antigen. Crossmatch was incompatible with all A RhD positive units. Management of such patient is extremely difficult due to the scarcity of Rh-D- donor blood. In this case, reference laboratory had one frozen Rh-D- blood ready for use if indicated. Fortunately, patient underwent caesarean section without any complication. Baby was grouped as A Rh-D positive with probable Rh genotype as CDe/-D-. Baby’s DCT was positive and eluate showed antibodies of identical reactivity as mother. Baby developed mild jaundice at day-2 and managed with phototherapy. Clinically Rh-D- phenotype in pregnant women can cause mild to fatal HDFN. Routine antibody screening in pregnant women can detect such rare case that helps proper management of mother and baby. Prior arrangement of this rare blood is warranted to prevent the maternal and infant mortality and morbidity.Bangladesh Journal of Medical Science Vol.20(3) 2021 p.669-672